Iberian moorings : Al-Andalus, Sefarad, and the tropes of exceptionalism - Brann, Ross, 1949- (Middle Ages series., 2021)
To Muslims the Iberian Peninsula was al-Andalus, to Jews it was Sefarad. Iberian Moorings traces how al-Andalus and Sefarad were invested with political, cultural, and historical significance across the Middle Ages and analyzes the tropes of Andalusi and Sefardi exceptionalism that linger in today's scholarship, literature, and film.